Complete mitochondrial genome organization of Tor putitora. (August 2014) - Sati, Jyoti; Goel, Chirag; Kumar, Rohit; Ali, S.; Patiyal, R. S.; Singh, Vijoy Kumar; Sahoo, Prabhati Kumari; Barat, Ashoktaru
Abstract The complete mitochondrial genome of Tor putitora, an endemic coldwater fish of Himalayas was determined for the first time. The genome is 16, 576 bp in length and consists of 13 protein coding genes, 22 tRNAs, 2 rRNA genes and 1 putative control region. The gene organization and its order were similar to other vertebrates. The overall base composition was; A: 31.9%, G: 15.6%, C: 27.5%, T: 25%, A + T content 56.9% and the G + C content 43.1%. The control region was also consisted of a microsatellite locus (TA) 13 between 16, 456 to 16, 481 bp. The present study will provide the rationale for the management and conservation of T. putitora.